Avaliação do potencial tecnológico da Pitanga (Eugenia uniflora L.) com base nas suas características anatômicas, físicas e químicas - Sikorsrki, Andrea Maria Pacheco (2010)
This study evaluated the nutritional and technological potential in pitanga (Eugenia uniflora L.), based on its anatomical, physical, chemical. and macroscopic features. Anatomical analysis showed that the pericarp, the edible part of the fruit, consists of parenchymatous mesocarp and exocarp and endocarp epidermis. In cross section it was observed that the epidermis is composed of a single layer of cells, which explains the fragility of the fruit handling, and coated with a thin layer of cuticle, which gives sleek appearance to the fruit. The epicarp cells presented anthocyanins and carotenoids, responsible for the typical color of the fruit. The mesocarp didn’t have sclerenchyma, consisting of parenchyma cells bulky, thin walls, with conspicuous intercellular spaces. The evaluation of the anthocyanin extracts stability of pitanga indicated good stability in acidic pH, with the perspective of use as a colorant in food products. The pitanga juice was obtained by enzymatic treatment yielding 50% , in relation to the pulp. Showed intense color, flavor and kept the peculiar aroma of the fruit and preserved 43.8% of the vitamin C and 77% of phenolic compounds. The addition of juice to green tea provided the development of a functional beverage with sensory acceptance. The pectins were extracted sequentially with water and citric acid 5%, resulting four fractions, while those from acid extraction had a high yield. The monosaccharide composition analysis showed that all pectic fractions werw performed by the same monosaccharides, in different proportions, with a predominance of galacturonic acid, the main constituent of the pectin chain. The presence of arabinofuranose was confirmed by nuclear magnetic resonance (NMR). All fractions showed a degree of esterification below 50% were classified as LM pectin (low degree of esterification). High pressure size exclusion chromatography coupled with multidetection system (HPSECMALLS/RI/UV) indicated that the fractions are polydisperse, with a predominance of populations with high and medium molar mass. The rheological behavior of the fractions at concentration 30g.L-1 and 20% sucrose, demonstrated that viscous solution or weak gels were obtained in the most of analysis. However, for fraction EIV V, storage modulus (G’) showed a weak dependence on frequency and was always higher than loss modulus (G”) over all frequency range, characteristic of typical, gel-like system. These results indicate that the pitanga has a high technological potential.